Object individuation is invariant to attentional diffusion: Changes in the size of the attended region do not interact with object-substitution masking - Goodhew, Stephanie C.; Edwards, Mark (Cognition, 2016)
When the human brain is confronted with complex and dynamic visual scenes, two pivotal processes are at play: visual attention (the process of selecting certain aspects of the scene for privileged processing) and object individuation (determining what information belongs to a continuing object over time versus what represents two or more distinct objects). Here we examined whether these processes are independent or whether they interact. Object-substitution masking (OSM) has been used as a tool to examine such questions, however, there is controversy surrounding whether OSM reflects object individuation versus substitution processes. The object-individuation account is agnostic regarding the role of attention, whereas object-substitution theory stipulates a pivotal role for attention. There have been attempts to investigate the role of attention in OSM, but they have been subject to alternative explanations. Here, therefore, we manipulated the size of the attended region, a pure and uncontaminated attentional manipulation, and examined the impact on OSM. Across three experiments, there was no interaction. This refutes the object-substitution theory of OSM. This, in turn, tell us that object-individuation is invariant the distribution of attention.